Small ubiquitin-like modifier 1 modification of pyruvate kinase M2 promotes aerobic glycolysis and cell proliferation in A549 human lung cancer cells - An, Shuxian (Onco Targets Ther, 2018)
OBJECTIVE: Lung cancer is the leading cause of cancer-related death worldwide. Aerobic glycolysis is considered the seventh hallmark of cancer. The M2 isoform of pyruvate kinase (PKM2) is an important rate-limiting enzyme in glycolytic pathway, and is strongly expressed in several types of cancer. Thus, understanding the underlying mechanisms of regulation of PKM2 is of great value for targeted therapy for lung cancer. PATIENTS AND METHODS: Seventy-three lung adenocarcinoma patients were analyzed in our study. The expression levels of PKM2 were analyzed by immunohistochemistry on tissues. The effect of small ubiquitin-like modifier 1 (SUMO1) on PKM2 expression was investigated using Western blot assay and quantitative polymerase chain reaction. PKM2 SUMO1 modification was determined by in vitro and in vivo SUMOylation assays. (18)F-deoxyglucose uptake and lactate production measurements were conducted to research the levels of glycolysis. The level of oxidative phosphorylation in cells was determined by cellular oxygen consumption rate measurements. Cell proliferation assays were carried out to confirm the growth ability of tumor cells. RESULTS: PKM2 was overexpressed in lung adenocarcinoma patients based on immunohistochemical staining. Patients with high PKM2 expression had reduced overall survival rate (P=0.017) and disease-free survival rate (P=0.027) compared with those with low PKM2 expression. SUMO1 promoted PKM2-dependent glycolysis. Western blotting analysis showed that SUMO1 knockdown in A549 cells led to a significant decrease in PKM2 protein expression. PKM2 could be covalently modified by SUMO1 at K336 (Lys336) site. SUMO1 modification of PKM2 at Lys-336 site increased glycolysis and promoted its cofactor functions. Moreover, PKM2 SUMO1 modification promoted the proliferation of A549 cells in vitro. CONCLUSION: This information is important in elucidating a new mechanism of regulation of PKM2, and suggested that SUMO1 modification of PKM2 could be a potential therapeutic target in lung cancer.